Penerapan Model Sains Teknologi Dan Masyarakat (STM) Untuk Menigkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Zainuddin, Zainuddin; Nabilla, Dinda (Faculty Of Education, 2024)
This research is undermined by the low Critical Thinking Ability of students on the learning of IPAS in Class IV UPT SDN 004 Salo. One solution to solving this problem is to use a model of Science and Technology Society. (STM). The study aims to enhance critical thinking skills using the Learning Model of Social Science Technology (STM) in IV grade students of UPT SDN 004 Salo. This research method is Class Action Research (PTK) which is carried out in two cycles consisting of two meetings and four stages, namely implementation planning, observation and reflection. The subject of this research is a student of class IV UPT 004 Salo It consists of 23 students there are 11 male students and 12 female students. Data collection methods use observation techniques, and documentation techniques. Research results show that using the Learning Model of Social Science Technology (STM) can improve students' ability to think critically. This is demonstrated by the obtaining of observation results at each cycle I meeting I of 23 students, it is known that the critical thinking ability of students that are included in the classification range reaches 7 people or 30% and the I cycle meeting II there are 9 people or 40%. Then cycle II meeting I there are 13 people or 56% who suffer from impotence and at cycle 2 meeting II increased to 20 people or 87%.